Determination of the Involvement of Autologous Mesenchymal Bone Marrow Stem Cells in Reparative Chondrogenesis - Kostrub, O.O.; Poliachenko, Yu.V.; Kotiuk, V.V.; Zasadniuk, I.A.; Blonskyi, R.I.; Smirnov, D.O. (TERRA ORTHOPAEDICA, 2020)
Summary. Articular cartilage injuries are observed in 60% of arthroscopies. Degenerative changes of the articular cartilage (osteoarthritis) is the most common disease of all the joints, which affects at least 10-13% of the population over the age of 60 years. Significant progress has been made in the treatment of pain and inflammation, but the evidence base for improving the articular cartilage repair remains weak. Despite the seemingly positive results of a number of studies on the use of mesenchymal stem cells (MSCs) for the articular cartilage restoration, the question of the nature of their participation in this process remains controversial. Objective. The objective of the study was to determine the involvement of autologous mesenchymal bone marrow stem cells in reparative chondrogenesis. Materials and Methods. Experimental and morphological determination of the participation of undifferentiated autologous bone marrow MSCs in reparative chondrogenesis was carried out on fifteen rabbits. MSCs of bone marrow marked with a red fluorescent dye PKH-26 (Sigma, USA) was injected into the cavity of the injured joint on the 3rd day after the articular cartilage defect formation. The presence of the transplanted labeled autologous MSCs was examined in these animals on cryostat sections on the seventh, fourteenth and twenty-first days after implantation with fluorescence microscopy. The characteristic red glow was observed in case of the presence of labeled cells in the regenerated cartilage tissue. Results. The presence of transplanted labeled autologous MSCs on cryostat sections was determined in all studied animals. On the 7th day, the cells were arranged diffusely, without noticeable accumulations. On the 14th day, the labeled cells fluoresced in the red zone of the spectrum and created compact conglomerates mainly at the defect zone. On the 21th day, the labeled cells were found only in the regenerate zone. The data obtained indicate the direct participation of autologous MSCs in the processes of chondroreparation after the exogenous implantation into the joint cavity. Conclusions. The method of autologous bone marrow MSCs labeling using PKH-26 fluorescent dyes has shown that autologous bone marrow MSCs are directly involved in the processes of chondroreparation when they are injected intraarticularly.